AÃ‡ÃƒO DE CINZAS DE INCINERADOR DE LIXO SÃ“LIDO URBANO COMO CORRETIVO DA ACIDEZ DE SOLOS - Chitolina, JosÃ© Carlos; Feliconio, Ana Elisa Galante; Carmo, JanaÃna Braga do; Oliveira, Fernando Carvalho; Lavorenti, Arquimedes (REVISTA DE AGRICULTURA, 2020)
AÇÃO DE CINZAS DE INCINERADOR DE LIXO SÓLIDO URBANO COMO CORRETIVO DA ACIDEZ DE SOLOS